Using trend models in Microsoft Excel to forecast various indicators ("Journal "U". Economy. Management. Finance.", 2025)
Analysis of time series using statistical approaches and creation of trend models on their basis to determine the values ​​of various parameters is a common practice. The article presents the development of trend models using Microsoft Excel software. In the process of solving a specific problem, the characteristics of trend stability (standard deviation, variation coefficient and average approximation error) were determined. The results of the study allowed us to make a number of reasonable conclusions.
Keywords: time series; trend; coefficient of determination; trend equation; trend stability indicators